2016
DOI: 10.1002/andp.201500350
|View full text |Cite
|
Sign up to set email alerts
|

Room‐temperature luminescence decay of colloidal semiconductor quantum dots: Nonexponentiality revisited

Abstract: While time-resolved luminescence spectroscopy is commonly used as a quantitative tool for the analysis of the dynamics of photoexcitation in colloidal semiconductor quantum dots, the interpretation of the virtually ubiquitous nonexponential decay profiles is frequently ambiguous, because the assumption of multiple discrete exponential components with distinct lifetimes for resolving the decays is often arbitrary. Here, an interpretation of the roomtemperature luminescence decay of CdSe/ZnS semiconductor quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 44 publications
4
25
0
11
Order By: Relevance
“…Therefore, this parameter is expected to increase as ν max lowers with an increase of the NC size. In accordance with this expectation, the TOPO‐capped CdSe NCs showed an increase of α from 0.20 to 0.33 as the average NC size increased from 2.5 nm to 5.0 nm . We should note that the a values derived in the present work for aqueous AIS NCs are much higher than those reported for CdSe‐TOPO NCs even at the lowest T studied.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, this parameter is expected to increase as ν max lowers with an increase of the NC size. In accordance with this expectation, the TOPO‐capped CdSe NCs showed an increase of α from 0.20 to 0.33 as the average NC size increased from 2.5 nm to 5.0 nm . We should note that the a values derived in the present work for aqueous AIS NCs are much higher than those reported for CdSe‐TOPO NCs even at the lowest T studied.…”
Section: Resultssupporting
confidence: 90%
“…We found that the PL decay curves of colloidal AIS NCs detected at different temperatures can be perfectly fitted with the Kohlrausch stretched exponential function (SI, Figure S9a). As in the case of TOPO‐capped CdSe NCs we found that the parameter β varies in the range of 0.5–0.6 with the temperature changes (SI, Figure S9b) indicating the same energy transfer mechanism as discussed in Ref. [42].…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations